Analysis of Phenotypic and Physiological Characteristics of Plant Height Difference in Alfalfa - Fang Jing; Shangli Shi; Yun A; Jian Guan; Baofu Lu; Bei Wu; Wenjuan Wang; Ruihong Ma; Pan Nan (Agronomy, 2023)
Cultivating new alfalfa (Medicago sativa L.) varieties with high yield and quality is of great significance for improving alfalfa yield and promoting the development of the grass and livestock industry. Plant height is an important indicator of alfalfa yield and is closely related to photosynthetic capacity, harvest index and yield. However, the underlying cause of the variation in height among alfalfa plants is not clear. In this paper, we measured the phenotypic traits, photosynthetic physiology and endogenous hormone content of tall- and short-stalked alfalfa materials and analyzed the important external and internal factors that caused the difference in plant height of alfalfa. We found that the phenotypic traits of tall- and short-stalked alfalfa materials showed significant differences, and dwarf alfalfa showed significant shortening of the main stem internode length. There were also some differences in light and physiological indicators and endogenous hormone contents between tall- and short-stalked alfalfa materials. Through correlation analysis, we found that the phenotypic traits and physiological indicators significantly correlated with alfalfa plant height were the number of internodes, stem diameter, average internode length, leaf–stem ratio, leaf area, Pn (net photosynthetic rate), Tr (transpiration rate), upper leaf SP (soluble protein), Suc (sucrose) content, middle stem Sta (starch) content, middle stem ZT (zeatin) and IAA (indole-3-acetic acid). Further analysis showed that Tr, IAA and LA played a direct role in plant height, with Tr contributing the most to plant height, followed by IAA. Finally, we found that the starch content of the middle stem had a significant impact on plant height through principal component analysis. These results provide new insights into the formation and genetic improvement of plant height traits in leguminous forages such as alfalfa.